Identification of factors affecting individual industries - Sadat Mirzadeh, Maryam (2017)
High knowledge and technology are rapidly becoming a competitive advantage in today’s world. Individual industries are considered one of the key sectors in the country’s industry. Ranking the factors that affect these industries makes us more familiar with their effectiveness and helps us take actions to improve such factors in knowledge-based companies. Consequently, based on previous research studies on Individual Industries, field observations, and a questionnaire prepared by the researchers, the current study explores and classifies the factors affecting the establishment of these industries. Regarding its purpose, this is an applied research, and regarding data collection, it is a descriptive survey. Using purposive sampling, 60 questionnaires were collected and effective factors were classified applying the SPSS software and the TOPSIS technique. This study suggests that content factors are ranked first place, while contextual and structural factors are ranked second and third, respectively. Therefore, executives and managers in single industries are recommended to strengthen joint enterprise norms and dominant values and beliefs in knowledge-based companies in order to help the growth and development of single industries.